Multiple Roles of Flagellar Export Chaperones for Efficient and Robust Flagellar Filament Formation in Salmonella - Minamino, Tohru; Morimoto, Yusuke V.; Kinoshita, Miki; Namba, Keiichi (Frontiers in Microbiology, 2021)
FlgN, FliS and FliT are flagellar export chaperones specific for FlgK/FlgL, FliC and FliD, respectively, which are essential component proteins for filament formation. These chaperones facilitate the docking of their cognate substrates to a transmembrane export gate protein, FlhA, to facilitate their subsequent unfolding and export by the flagellar type III secretion system (fT3SS). Dynamic interactions of the chaperones with FlhA are thought to determine the substrate export order. To clarify the role of flagellar chaperones in filament assembly, we constructed cells lacking FlgN, FliS and/or FliT. Removal of either FlgN, FliS or FliT resulted in leakage of a large amount of unassembled FliC monomers into the culture media, indicating that these chaperones contribute to robust and efficient filament formation. The ∆flgN ∆fliS ∆fliT (∆NST) cells produced short filaments similarly to the ∆fliS mutant. Suppressor mutations of the ∆NST cells, which lengthened the filament, were all found in FliC and destabilized the folded structure of FliC monomer. Deletion of FliS inhibited FliC export and filament elongation only after FliC synthesis was complete. We propose that FliS is not involved in the transport of FliC upon onset of filament formation but FliS-assisted unfolding of FliC by the fT3SS becomes essential for its rapid and efficient export to form a long filament when FliC becomes fully expressed in the cytoplasm.